High-molecular functional coating material, high-molecular functional coating as well as preparation method and application of high-molecular functional coating

By introducing catechol and its derivative structure into polymer functional coating materials and adopting reversible addition-break chain transfer polymerization reaction, the problems of cumbersome coating construction steps and poor uniformity in the prior art are solved, and the problem of coating construction steps is achieved. Efficient, uniform coating coverage and stable performance improvements.

CN119391250AActive Publication Date: 2025-02-07UNIV OF SCI & TECH OF CHINA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411575696.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing polymer functional coating technology has complicated steps when building coatings, and poor bonding of adhesion molecules and functional molecules, resulting in poor coating uniformity on the surface of complex-shaped materials, local performance failure, and poor biocompatibility.

Method used

Reversible addition-break chain transfer agent with catechol and its derivative structure and functional monomer are used to perform reversible addition-break chain transfer polymerization reaction to prepare polymerization of polymerized polymers and coated in one step. The process forms a uniform coating on the surface of the substrate.

Benefits of technology

The coating preparation process is simplified, the uniformity and stability of the coating covering the surface of a variety of substrates is improved, the risks of local failure and biocompatibility differences are reduced, and the compatibility and applicability of the coating is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391250A_ABST
    Figure CN119391250A_ABST
Patent Text Reader

Abstract

The invention discloses a high-molecular functional coating material, a high-molecular functional coating as well as a preparation method and application of the high-molecular functional coating material. The high-molecular functional coating material has the following structure: # imgabs0 #, wherein R comprises any one or a combination of more than two of a group containing a thioether structure, a group containing a sulfonium ion structure, a group containing a sulfoxide structure, a group containing a sulfone structure, a group containing a zwitter-ion structure and a group containing an oligo-ethylene glycol structure; n is any integer selected from 1-200; x and y represent the molar ratio of copolymerization units, x + y = 1, 0 < = x < 1, and 0 < y < = 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer coatings and biomedical materials, and specifically relates to a polymer functional coating material, a polymer functional coating, and a preparation method and application thereof. Background Art

[0002] The application of polymer functional coating technology in the field of medical materials has been one of the important research directions of biomedical engineering in recent decades. With the aging of the population and the rising prevalence of chronic diseases, the demand for medical devices and implants continues to increase. In the cardiovascular field, thrombosis is one of the main risks threatening the life safety of patients. Medical devices that are in direct contact with blood, such as artificial heart valves, vascular stents and extracorporeal circulation equipment, are in urgent need of surface treatment technology with lasting anticoagulant properties. Hospital infection control has always been a major problem in clinical work. According to statistics, millions of patients are affected by medical-related infections every year, which not only prolongs hospital stays and increases medical expenses, but may also lead to serious complications or even death. In addition, the biofilm formed after bacterial infection is a complex structure formed by the attachment and growth of microorganisms on the surface of implants. It is one of the important causes of implant infection and loss of function. Therefore, it is imperative to develop medical device surface treatment technology with lasting antibacterial properties. In key medical fields such as organ transplantation and biosensors, effectively reducing the body's rejection of foreign bodies and significantly extending the actual service life of implants are the core elements to improve treatment effectiveness. Therefore, these fields have higher requirements for biocompatibility than general medical devices.

[0003] In the face of these clinical challenges, polymer functional coating technology has emerged and has made significant progress in recent decades. Whether in the fields of in vivo implants, in vitro diagnostic and therapeutic equipment, or wound dressings and skin repair, polymer functional coatings have provided important support and innovative solutions for the development of biomedical technology and the improvement of clinical treatment effects. This technology forms a thin film with specific functions on the surface of medical materials, while retaining the excellent mechanical properties of the substrate, significantly improving the biological properties of the surface. However, the existing technology usually constructs a polymer functional coating by first covering the polymer adhesion layer and then coating the functional coating. The traditional multi-step coating method requires complex pretreatment of the substrate, intermediate layer coating and other steps, and the steps are cumbersome; due to the step-by-step coating, the adhesion molecules and functional molecules in the coating have poor binding properties, which leads to poor coating uniformity on the surface of materials with more complex shapes. Due to local performance differences, potential problems such as local failure, uneven wear or biocompatibility differences may occur, thereby affecting the performance of the coating. Summary of the invention

[0004] The main purpose of the present invention is to provide a polymer functional coating material, a polymer functional coating and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] One aspect of the present invention provides a polymer functional coating material, wherein the polymer functional coating material has a structure as shown in formula (I):

[0007]

[0008] Wherein, R includes any one or a combination of two or more of a group containing a thioether structure, a group containing a sulfonium ion structure, a group containing a sulfoxide structure, a group containing a sulfone structure, a group containing a zwitterionic structure, and a group containing an oligoethylene glycol structure; n is selected from any integer between 1 and 200; x and y represent the molar ratio of the copolymer units, x+y=1, 0≤x<1, 0<y≤1.

[0009] Another aspect of the present invention provides a method for preparing a polymer functional coating material, which comprises: mixing a chain transfer agent having a catechol and / or catechol derivative structure with a functional monomer, and performing a reversible addition-fragmentation chain transfer polymerization reaction to obtain a polymer functional coating material.

[0010] Another aspect of the present invention also provides a polymer functional coating material prepared by the aforementioned preparation method.

[0011] Another aspect of the present invention also provides a polymer functional coating, which is obtained by applying the aforementioned polymer functional coating material to the surface of a substrate; the thickness of the coating is 100-2000nm.

[0012] Another aspect of the present invention also provides a method for preparing the aforementioned polymer functional coating, which comprises: performing a hydroxylation hydrophilic modification treatment on the surface of a substrate, and then applying the polymer functional coating material to the surface of the substrate in a buffer system to obtain the polymer functional coating.

[0013] Another aspect of the present invention also provides the use of the aforementioned polymer functional coating material or the aforementioned polymer functional coating in the field of medical material protection.

[0014] Compared with the prior art, the technical solution of the present invention has at least the following advantages:

[0015] The polymer functional coating material provided by the present invention has a chemical structure inspired by mussel adhesion. The coating can be completed in one step by immersing the synthesized polymer functional coating material and a medical substrate into a buffer solution, and the coating can be smoothly applied on the surfaces of substrates of various materials. The catechol and its derivative structures protected by TBS groups in the molecular structure can effectively avoid oxidation and self-polymerization of catechol and its derivatives. In particular, the protected catechol and its derivatives are introduced into a reversible addition-fragmentation chain transfer agent to synthesize polymers with clear main chain structures, and the monomers have good compatibility and can be polymerized with a variety of functional monomers. In practical applications, the cumbersome steps involved in coating construction can be greatly reduced. On the surfaces of metal materials and some special non-metallic materials, the polymer coating material of the present invention can effectively form a stable coating, thereby providing a more concise, efficient and widely applicable method for preparing a uniform coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1a This is a nuclear magnetic hydrogen spectrum of a reversible addition-fragmentation chain transfer agent molecule having the structure of catechol and its derivatives in a typical embodiment of the present invention;

[0018] Figure 1b This is a carbon NMR spectrum of a reversible addition-fragmentation chain transfer agent molecule having the structure of catechol and its derivatives in a typical embodiment of the present invention;

[0019] Figure 1c This is a mass spectrometry characterization diagram of a reversible addition-fragmentation chain transfer agent molecule having the structure of catechol and its derivatives in a typical embodiment of the present invention;

[0020] Figure 2 This is a hydrogen nuclear magnetic spectrum of a monomer molecule having the structure of catechol and its derivatives in a typical embodiment of the present invention;

[0021] Figure 3a is the nuclear magnetic hydrogen spectrum of the hydrophobic polymer coating material molecule in Example 1 of the present invention;

[0022] Figure 3b This is a GPC characterization diagram of the hydrophobic polymer coating material molecules in Example 1 of the present invention;

[0023] Figure 4aThe nuclear magnetic hydrogen spectrum of the sulfonium ion-containing antibacterial polymer coating material molecule in Example 1 of the present invention;

[0024] Figure 4b This is a GPC characterization diagram of the antibacterial polymer coating material molecule containing sulfonium ions in Example 1 of the present invention;

[0025] Figure 5a is the H-NMR spectrum of the hydrophilic polymer coating material molecule in Example 2 of the present invention;

[0026] Figure 5b This is a GPC characterization diagram of the hydrophilic polymer coating material molecules in Example 2 of the present invention;

[0027] Figure 6a This is the nuclear magnetic hydrogen spectrum of the hydrophilic polymer coating material molecule with a degree of polymerization of 33 in Example 3 of the present invention;

[0028] Figure 6b This is the nuclear magnetic hydrogen spectrum of the hydrophilic polymer coating material molecule with a degree of polymerization of 70 in Example 3 of the present invention;

[0029] Figure 6c This is the nuclear magnetic hydrogen spectrum of the hydrophilic polymer coating material molecule with a degree of polymerization of 101 in Example 3 of the present invention;

[0030] Figure 6d This is the nuclear magnetic hydrogen spectrum of the hydrophilic polymer coating material molecule with a degree of polymerization of 195 in Example 3 of the present invention;

[0031] Figure 6e This is a GPC characterization diagram of the hydrophilic polymer coating material molecules with different polymerization degrees in Example 3 of the present invention;

[0032] Figure 7 is the nuclear magnetic hydrogen spectrum of the sulfone-containing polymer coating material molecule in Example 4 of the present invention;

[0033] Figure 8 is the H NMR spectrum of the zwitterionic polymer coating material molecule in Example 5 of the present invention;

[0034] Fig. 9 This is the H-NMR spectrum of the oligoethylene glycol polymer coating material molecule in Example 6 of the present invention;

[0035] Fig.10 The X-ray photoelectron spectrum and the table of the contents of each element of the polymer coating constructed by using the hydrophilic polymer coating material in Example 2 in Example 11 of the present invention;

[0036] Fig.11 The platelet adhesion test results of the polymer coating constructed with the hydrophilic polymer coating material in Example 2 in Example 11 of the present invention;

[0037] Fig.12 The results of the PAO1 bacterial adhesion experiment of the polymer coating constructed with the hydrophilic polymer coating material in Example 2 in Example 11 of the present invention;

[0038] Fig.13 The laser confocal microscopy result of the Escherichia coli adhesion experiment of the polymer coating constructed with the hydrophilic polymer coating material in Example 2 in Example 11 of the present invention;

[0039] Fig.14 Schematic diagram of a polymer coating prepared in a typical embodiment of the present invention to resist bacterial adhesion. DETAILED DESCRIPTION

[0040] The present invention will be more fully understood by reading the following specific embodiments. However, it should be understood that the specific embodiments disclosed below are only exemplary of the present invention, and the present invention can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0041] As one aspect of the technical solution of the present invention, a polymer functional coating material is provided having a structure as shown in formula (I):

[0042]

[0043] Wherein, R includes but is not limited to any one or a combination of two or more of a group containing a thioether structure, a group containing a sulfonium ion structure, a group containing a sulfoxide structure, a group containing a sulfone structure, a group containing a zwitterionic structure, and a group containing an oligoethylene glycol structure; n is selected from any integer between 1 and 200; x and y represent the molar ratio of the copolymerized units, x+y=1, 0≤x<1, 0 <y≤1。

[0044] As another aspect of the technical solution of the present invention, a method for preparing a polymer functional coating material involves: mixing a chain transfer agent having a catechol and / or catechol derivative structure with a functional monomer, performing a reversible addition-fragmentation chain transfer polymerization reaction, and obtaining a polymer functional coating material.

[0045] It should be noted that, although in the prior art, monomers containing catechol structures and monomers containing zwitterionic groups can be polymerized, monomers synthesized from catechol derivative structures do not have good copolymerization compatibility with all functional monomers. The present invention introduces catechol and its derivatives into reversible addition-fragmentation chain transfer agents (RAFT agents) to synthesize polymers with clear main chain structures. This property brings significant compatibility advantages to coating technology. The reversible addition-fragmentation chain transfer agent of the present invention can provide a wide range of monomer compatibility and can be further polymerized with a variety of functional monomers, thereby preparing a polymer functional coating material that is stably bonded to a substrate and has certain functions.

[0046] In some embodiments, the preparation method includes: mixing a chain transfer agent having a catechol and / or a catechol derivative structure, a monomer having a catechol and / or a catechol derivative structure, and a functional monomer, and performing a reversible addition-fragmentation chain transfer polymerization reaction to obtain a polymer functional coating material.

[0047] The reaction of the present invention can also be performed without adding catechol and / or catechol derivative structure monomers, and a high molecular functional coating material can also be obtained. Adding them can increase the coating rate and stability after coating, and not adding them will not affect its intrinsic properties.

[0048] In some preferred embodiments, the functional monomers include but are not limited to any one or a combination of two or more of monomers containing thioether structures, monomers containing sulfonium ion structures, monomers containing sulfoxide structures, monomers containing sulfone structures, monomers containing zwitterion structures, and monomers containing oligoethylene glycol structures.

[0049] The present invention provides compatibility for coatings on the surfaces of different materials through a mussel-inspired polymer structure, and prepares a polymer coating material having a structure of catechol and its derivatives through reversible addition-fragmentation chain transfer polymerization, wherein functional monomers are used as selections under specific needs to give the coating functions to cope with different scenarios. For example, a thioether structure can give the coating hydrophobic properties, a sulfonium ion structure can give the coating antibacterial properties because cations can kill bacteria, a sulfoxide structure can give the coating hydrophilic properties, a sulfone structure can resist protein adhesion, a zwitterionic structure can give the coating a wide range of antifouling properties, and an oligoethylene glycol structure can give the coating both good biocompatibility and a certain degree of hydrophilicity.

[0050] Furthermore, the monomer containing a thioether structure has a structure as shown in formula (1):

[0051]

[0052] Furthermore, the monomer containing the sulfonium ion structure has a structure as shown in formula (2):

[0053]

[0054] Furthermore, the monomer containing a sulfoxide structure has a structure as shown in formula (3):

[0055]

[0056] Furthermore, the monomer containing a sulfone structure has a structure as shown in formula (4) or formula (5):

[0057]

[0058] Furthermore, the monomer containing a zwitterionic structure has a structure as shown in at least any one of formula (6) to formula (11):

[0059]

[0060] Furthermore, the monomer containing the oligoethylene glycol structure has a structure as shown in formula (12):

[0061]

[0062] In formula (12), n is any integer selected from 1 to 50.

[0063] In some preferred embodiments, the molar ratio of the chain transfer agent having a catechol and / or a catechol derivative structure, the monomer having a catechol and / or a catechol derivative structure, and the functional monomer is (1-5):(1-30):(10-200).

[0064] In some preferred embodiments, the polymerization temperature of the reversible addition-fragmentation chain transfer polymerization is 70-80° C., and the polymerization time is 6-12 h.

[0065] In some preferred embodiments, the chain transfer agent having a catechol and / or catechol derivative structure has a structure as shown in formula (II):

[0066]

[0067] In some preferred embodiments, the monomer having a catechol and / or catechol derivative structure has a structure as shown in at least one of formula (III) or formula (IV):

[0068]

[0069] The catechol and / or catechol derivative structures protected by TBS in the present invention are beneficial to the synthesis of polymers (phenolic hydroxyl group inhibition), which can prevent catechol and its derivatives from self-polymerizing and affecting the coating properties, so that the coating material can be stored for a long time. When used, the silane protection is removed and the coating material is used immediately to ensure effectiveness.

[0070] In some embodiments, the preparation method includes: mixing a chain transfer agent having a catechol and / or a catechol derivative structure, a monomer having a catechol and / or a catechol derivative structure, a functional monomer, a polymerization initiator and a solvent to form a mixed reaction system, and performing a reversible addition-fragmentation chain transfer polymerization reaction to obtain a polymer functional coating material.

[0071] In some preferred embodiments, the polymerization initiator includes but is not limited to azobisisobutyronitrile (AIBN).

[0072] In some preferred embodiments, the molar ratio of the polymerization initiator to the chain transfer agent having a catechol and / or catechol derivative structure is 0.1-0.5:1-10.

[0073] In some preferred embodiments, the solvent includes but is not limited to dimethyl sulfoxide (DMSO).

[0074] In some preferred embodiments, the mass volume ratio of the mixed reaction system to the solvent is (10-1200) mg: (100-1200) μL.

[0075] As another aspect of the technical solution of the present invention, it also relates to a polymer functional coating material prepared by the aforementioned preparation method.

[0076] As another aspect of the technical solution of the present invention, a polymer functional coating is obtained by applying the aforementioned polymer functional coating material to the surface of a substrate; a coating with a thickness of 100-2000nm can be constructed according to the coating immersion time.

[0077] As another aspect of the technical solution of the present invention, it also involves a method for preparing the aforementioned polymer functional coating, which includes: performing hydroxylation hydrophilic modification treatment on the surface of the substrate, and then applying the polymer functional coating material to the surface of the substrate in a buffer system to obtain the polymer functional coating.

[0078] In some embodiments, the preparation method specifically comprises:

[0079] (1) Using an oxygen plasma cleaning machine to perform hydroxylation and hydrophilic modification on the surface of a substrate (e.g., a medical material) so that the surface of the substrate is rich in hydroxyl groups; oxygen plasma cleaning first performs surface hydroxylation modification on the material base, which can improve the coating efficiency and coating bonding stability;

[0080] (2) The polymer functional coating material is dissolved in a buffer system to obtain a mixed solution, and the substrate is immersed in the mixed solution, thereby constructing the polymer functional coating on the surface of the medical material in one step.

[0081] The one-step coating process of the present invention greatly simplifies the coating preparation process. The one-step coating process is achieved by means of the catechol derivative structure contained in the polymer functional coating. Compared with the traditional multi-step coating method, there is no need for complicated pretreatment, intermediate layer coating and other tedious steps, and only one-step operation is required to evenly form a coating on the surface of the biomaterial. This not only improves production efficiency, saves time and labor costs, but also reduces errors and quality instability factors that may be introduced due to multi-step operations. In large-scale production, this high efficiency and convenience advantage is particularly prominent, and can quickly meet the market demand for medical material coatings.

[0082] Furthermore, through a precisely controlled one-step coating process, the coating can be evenly distributed on the surface of the biomaterial. Whether the shape of the material is regular or complex, such as implants with tiny pores or curved structures, uniform coating coverage can be achieved. This uniformity is critical to the performance of the coating, ensuring that the biomaterial can obtain the same protection and functional improvement in all parts, avoiding potential problems caused by local performance differences, such as local corrosion, uneven wear or differences in biocompatibility, thereby improving the overall quality and reliability of the product.

[0083] In some embodiments, the substrate includes, but is not limited to, any one or a combination of two or more of polyethylene, polypropylene, polyvinyl chloride, polytetrafluoroethylene, expanded polytetrafluoroethylene, polylactic acid, polycarbonate, polyurethane, polystyrene, polysulfone, polyethersulfone, polyacrylonitrile, polymethacrylate, latex, silicone rubber, glass, ceramic, stainless steel, titanium alloy, and nickel-titanium alloy.

[0084] In some embodiments, the hydroxylation hydrophilic modification treatment includes: placing the substrate in a vacuum plasma cleaner, subjecting the substrate to oxygen plasma treatment at a radio frequency power of 100-300 W and a gas flow rate of 100-500 mL / min to obtain a hydroxyl-rich hydrophilic surface.

[0085] In some embodiments, the buffer system includes but is not limited to a tris(hydroxymethyl)aminomethane solution buffer system.

[0086] In some preferred embodiments, the concentration of tris(hydroxymethyl)aminomethane in the buffer system is 10-20 mM.

[0087] In some embodiments, the pH value of the buffer system is 8-9.

[0088] As another aspect of the technical solution of the present invention, it also involves the application of the aforementioned polymer functional coating material or the aforementioned polymer functional coating in the field of medical material protection.

[0089] In summary, the present invention proposes a polymer functional coating that can be coated in one step, which is mainly composed of two components, one is a polymer monomer that provides functionality to the coating, and the other is catechol and its derivatives for realizing a one-step coating process. Functional monomers with corresponding proportions are selected according to specific application requirements, and reversible addition-fragmentation chain transfer agents are combined with catechol derivative monomers for reversible addition-fragmentation chain transfer polymerization to synthesize corresponding polymer coating materials. After a simple deprotection procedure, the coating construction can be completed in one step under a simple biological buffer system. This technology provides a wide range of functional tool libraries for material surface functionalization, which can be customized and synthesized according to different medical needs to achieve precise functionalization. At the same time, compared with existing processes, this technology significantly simplifies the coating preparation process, and at the same time shows excellent compatibility and wide applicability to a variety of substrate materials.

[0090] The polymer functional coating material with one-step coating function provided by the present invention can customize polymer coatings with different functions according to functional requirements for different application scenarios, and form a layer of polymer film with specific functions on the surface of medical materials, thereby giving medical devices or implants new properties, such as antibacterial, anticoagulant, biocompatibility, etc.

[0091] The polymer functional coating material with one-step coating function provided by the present invention effectively solves many pain points in the biomedical industry through its unique advantages and scalable functionality, as well as innovative polymer design and controllable synthesis and process. It has broad application prospects and huge market value, and will make important contributions to promoting the advancement of biomedical technology and improving the quality of life of patients.

[0092] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The reagents and raw materials used in the following examples are commercially available, and the experimental methods without specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0093] For example, the reversible addition-fragmentation chain transfer agent having the structure of catechol and its derivatives used in the embodiments of the present invention can be synthesized by the following steps:

[0094]

[0095] The specific preparation method is as follows: 0.69g CTA is dissolved in 20mL DCM and stirred to dissolve, 0.81g EDC is added to activate the carboxyl group for 30min, 1g silane-protected catechol and its derivatives (DA-TBS) are dissolved in 10mL DCM and added to a flask, 0.06g DMAP is added to catalyze the reaction, and after overnight reaction, the solvent is removed under reduced pressure, and then further purified by column chromatography (PE: EA = 10: 1) to obtain a yellow product CTA-DA-TBS (1.11g, yield: 67.3%). Its structure and purity are verified by nuclear magnetic hydrogen spectrum, carbon spectrum and mass spectrum, and the results are as follows: Figure 1a , Figure 1b and Figure 1c shown.

[0096] For example, the monomers having the structure of catechol and its derivatives used in the embodiments of the present invention can be synthesized by the following steps:

[0097]

[0098] The specific preparation method is as follows: 3g TBS-protected catechol and its derivatives and 30mL DCM are added to a flask and placed in an ice bath. 0.79g triethylamine is added to the flask and then 0.72g acryloyl chloride is added dropwise. The reaction ends after 3h. The flask is washed with a saturated sodium bicarbonate aqueous solution and separated. The organic phase is dried with anhydrous sodium sulfate, the solvent is removed under reduced pressure, and then further purified by column chromatography (PE: EA = 1: 1) to obtain a light brown solid product (3.15g, yield: 92%). Its structure and purity are verified by nuclear magnetic hydrogen spectrum, and the results are as follows: Figure 2 shown.

[0099] Example 1

[0100] This embodiment provides a method for preparing a hydrophobic polymer coating material (containing a thioether structure) that can be coated in one step, and the reaction synthesis process is as follows:

[0101]

[0102] The specific steps are as follows: ethyl 2-(methylthio)acrylate (298 mg, 100 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalents) were dissolved in 0.3 mL DMSO and added to a polymerization reaction tube. The reaction tube was degassed by repeating the freeze-degassing-thawing cycle three times and sealed under vacuum. The polymer reaction solution was reacted at 70°C for 8 hours, the polymerization reaction was quenched with liquid nitrogen, and the reaction tube was opened. The solution was precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle was repeated three times, and the filter cake was then collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a yellow product. Its structure and molecular weight distribution were characterized by hydrogen nuclear magnetic resonance spectroscopy and GPC, and the results were as follows. Figure 3a , Figure 3b When constructing the coating, the hydrophobic polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0103] In addition, the obtained yellow product can be subjected to a methylation reaction to obtain an antibacterial polymer coating material containing sulfonium ions. The reaction synthesis process is as follows:

[0104]

[0105] The specific steps are as follows: the yellow product (200 mg, 1 equivalent) obtained above was dissolved in 2 mL DMF, methyl iodide (20 mg, 10 equivalents) was added, and the mixture was reacted at 90° C. for 8 hours. The organic solvent was removed by dialysis and then freeze-dried to obtain a white powder product, whose structure and molecular weight distribution were characterized by hydrogen spectrum and GPC. The results were as follows: Figure 4a , Figure 4b shown.

[0106] Example 2

[0107] This embodiment provides a method for preparing a hydrophilic polymer coating material (containing a sulfoxide structure) that can be coated in one step. The reaction synthesis process is as follows:

[0108]

[0109] The specific steps are as follows: ethyl 2-(methylsulfonyl)acrylate (517 mg, 100 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalents) were dissolved in 0.3 mL DMSO and added to a polymerization reaction tube. The reaction tube was degassed by repeating the freeze-degassing-thawing cycle three times and sealed under vacuum. The polymer reaction solution was reacted at 70°C for 8 hours, the polymerization reaction was quenched with liquid nitrogen, and the reaction tube was opened. The solution was precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle was repeated three times, and the filter cake was then collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a yellow product. Its structure and molecular weight distribution were characterized by hydrogen nuclear magnetic resonance spectroscopy and GPC, and the results were as follows. Figure 5a , Figure 5b When constructing the coating, the hydrophilic polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0110] Example 3

[0111] This embodiment provides a method for preparing a hydrophilic polymer coating material having different molecular weights that can be coated in one step.

[0112] According to the preparation method in Example 2, polymers with different degrees of polymerization (33, 70, 101, and 195, respectively) were synthesized by adjusting the equivalent ratio between the polymerization monomer 2-(methylsulfonyl)ethyl acrylate and CTA-DA-TBS as a chain transfer agent.

[0113] The specific steps are as follows: the equivalents of 2-(methylsulfonyl)ethyl acrylate (155 mg, 30 equivalents, 362 mg, 70 equivalents, 517 mg, 100 equivalents, 1034 mg, 200 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalents) are regulated and dissolved in 0.3 mL DMSO, and added to a polymerization reaction tube. The reaction tube is degassed by repeating a freeze-degassing-thawing cycle three times and sealed under vacuum. The polymer reaction solution is reacted at 70°C for 8 hours, the polymerization reaction is quenched with liquid nitrogen, and the reaction tube is opened. The solution is precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle is repeated three times, and then the filter cake is collected by filtration and dried in a vacuum oven at room temperature overnight to obtain yellow products with different degrees of polymerization. Its structure and molecular weight distribution are characterized by hydrogen nuclear magnetic resonance spectroscopy and GPC, and the results are as follows. Figure 6a , Figure 6b , Figure 6c , Figure 6d , Figure 6e As shown, Figure 6epDMSO-33, pDMSO-70, pDMSO-101, and pDMSO-195 respectively represent polymers with a degree of polymerization of 33, 70, 101, and 195. When constructing the coating, the hydrophilic polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0114] Example 4

[0115] This embodiment provides a method for preparing a sulfone-containing polymer coating material that can be coated in one step. The reaction synthesis process is as follows:

[0116]

[0117] The specific steps are as follows: 2-(methylsulfonyl)ethyl methacrylate (184 mg, 30 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalents) were dissolved in 0.3 mL DMSO and added to a polymerization reaction tube. The reaction tube was degassed by repeating the freeze-degassing-thawing cycle three times and sealed under vacuum. The polymer reaction solution was reacted at 70°C for 8 hours, the polymerization reaction was quenched with liquid nitrogen, and the reaction tube was opened. The solution was precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle was repeated three times, and the filter cake was then collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a white product. Its structure was characterized by hydrogen nuclear magnetic resonance spectroscopy, and the results are as shown Figure 7 When constructing the coating, the sulfone-containing polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0118] Example 5

[0119] This embodiment provides a method for preparing a zwitterionic polymer coating material that can be coated in one step, and the reaction synthesis process is as follows:

[0120]

[0121] The specific steps are: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid salt (267 mg, 30 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalent) were dissolved in 0.3 mL DMSO and added to the polymerization reaction tube. The reaction tube was degassed by repeating the freeze-degassing-thawing cycle three times and sealed under vacuum. The polymer reaction solution was reacted at 70°C for 8 hours, the polymerization reaction was quenched with liquid nitrogen, and the reaction tube was opened. The solution was precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle was repeated three times, and then the filter cake was collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a white product. Its structure was characterized by hydrogen nuclear magnetic resonance spectroscopy, and the results are as shown Figure 8 When constructing the coating, the zwitterionic polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0122] Example 6

[0123] This embodiment provides a method for preparing an oligoethylene glycol polymer coating material that can be coated in one step, and the reaction synthesis process is as follows:

[0124]

[0125] The specific steps are as follows: poly(ethylene glycol) methyl ether methacrylate (797 mg, 60 equivalents), N-(3,4-bis(tert-butyldimethylsilyloxy)phenethyl) acrylamide (417 mg, 30 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalent) were dissolved in 0.3 mL DMSO and added to a polymerization reaction tube. The reaction tube was degassed by repeating a freeze-degassing-thawing cycle three times and sealed under vacuum. The polymer reaction solution was reacted at 70°C for 8 hours, the polymerization reaction was quenched with liquid nitrogen, and the reaction tube was opened. The solution was precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle was repeated three times, and then the filter cake was collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a white product. Its structure was characterized by hydrogen nuclear magnetic resonance spectroscopy, and the results are as follows Fig. 9 When constructing the coating, the oligoethylene glycol polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0126] Example 7

[0127] This embodiment provides a method for preparing an oligoethylene glycol polymer coating material that can be coated in one step, and the reaction synthesis process is as follows:

[0128]

[0129] The specific steps are as follows: poly(ethylene glycol) methyl ether methacrylate (275 mg, 20 equivalents), AIBN (1.1 mg, 0.2 equivalents) and CTA-DA-TBS (20 mg, 1 equivalent) are dissolved in 0.3 mL DMSO and added to a polymerization reaction tube, which is degassed by freezing-degassing-thawing cycles three times and sealed under vacuum. The polymer reaction solution is reacted at 75 ° C for 12 hours, the polymerization reaction is quenched with liquid nitrogen, and the reaction tube is opened. The solution is precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle is repeated three times, and then the filter cake is collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a light yellow product. When constructing the coating, the oligoethylene glycol polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0130] Example 8

[0131] This embodiment provides a method for preparing a sulfonium ion polymer coating material that can be coated in one step. The reaction synthesis process is as follows:

[0132]

[0133] The specific steps are as follows: (2-(acryloyloxy)ethyl)dimethylsulfonium (643 mg, 10 equivalents), AIBN (6.5 mg, 0.1 equivalents) and CTA-DA-TBS (250 mg, 1 equivalents) are dissolved in 0.5 mL DMSO and added to a polymerization reaction tube, which is degassed by freezing-degassing-thawing cycles three times and sealed under vacuum. The polymer reaction solution is reacted at 80°C for 8 hours, the polymerization reaction is quenched with liquid nitrogen, and the reaction tube is opened. The solution is precipitated into an excess of ether solution (40 mL). The above dissolution-precipitation cycle is repeated three times, and then the filter cake is collected by filtration and dried in a vacuum oven at room temperature overnight to obtain a white product. When constructing the coating, the sulfonium ion polymer coating material is placed in a 1 mM p-toluenesulfonic acid DCM solution to remove the silane protecting group, and the solvent is removed under reduced pressure before use.

[0134] Example 9

[0135] Compared with Example 6, the difference is that poly(ethylene glycol) methyl ether methacrylate (60 equivalents), N-(3,4-bis(tert-butyldimethylsilyloxy)phenethyl)acrylamide (15 equivalents), AIBN (0.1 equivalents) and CTA-DA-TBS (3 equivalents) are dissolved in 1 mL of DMSO. The polymer reaction solution is reacted at 80° C. for 6 hours.

[0136] Example 10

[0137] Compared with Example 6, except that poly(ethylene glycol) methyl ether methacrylate (60 equivalents), N-(3,4-bis(tert-butyldimethylsilyloxy)phenethyl)acrylamide (1 equivalent), AIBN (0.2 equivalents) and CTA-DA-TBS (1 equivalent) were dissolved in 0.1 mL DMSO.

[0138] Embodiment 11

[0139] This embodiment provides a method for preparing a hydrophilic polymer coating, and the specific steps include:

[0140] Various substrates were placed in a vacuum plasma cleaning device. When the radio frequency power was set to 300W and the gas flow rate was maintained at 100mL / min, the medical materials were treated with oxygen plasma to obtain a hydroxyl-rich hydrophilic surface. Next, a 10mM tris(hydroxymethyl)aminomethane solution (121mg / 100mL) was used as a buffer system, and the pH value of the solution was adjusted to 8.5. Subsequently, the hydrophilic polymer coating material from which the silane protection was removed in Example 2 was dissolved in the above buffer system and configured to 2mg / mL. The medical material treated with oxygen plasma was immersed in the aforementioned solution and the reaction was allowed to continue for 24 hours. When the reaction was terminated, an ultrasonic cleaning operation was performed, and then the material was dried with nitrogen for subsequent use. The results were verified by X-ray photoelectron spectroscopy, and the results were as follows. Fig.10 As shown, Bare represents untreated medical materials, and pDMSO represents medical materials after coating construction, wherein the increase of sulfur element confirms the effective construction of the coating.

[0141] Example 12

[0142] When preparing the coating, the density of surface hydroxylation can be controlled by adjusting the radio frequency power and air flow rate of the plasma cleaning machine. Furthermore, the binding rate of the surface coating on the hydroxyl-rich surface can be controlled by adjusting the concentration of the tris(hydroxymethyl)aminomethane solution and the immersion time, thereby affecting the construction thickness of the coating.

[0143] The specific steps are: the medical tubing is treated under the condition that the radio frequency power is set to 100W and the gas flow rate is maintained at 100mL / min, and then a 10mM tris(hydroxymethyl)aminomethane solution is used as a buffer system, and the hydrophilic polymer coating material without silane protection in Example 2 is dissolved in the above buffer system and configured to 2mg / mL, and the medical material treated with oxygen plasma is immersed in the above-configured solution, and the reaction is allowed to continue for 6 hours, and a functional coating with a coating thickness of about 100nm can be obtained; without changing other conditions, the concentration of the tris(hydroxymethyl)aminomethane solution is increased to 20mM. After the same 6-hour immersion, a functional coating of about 500nm can be obtained; without changing other conditions, the radio frequency power is set to 200W and the gas flow rate is maintained at 500mL / min. After the same 6-hour immersion, a functional coating of about 1000nm can be obtained.

[0144] Example 13

[0145] Compared with Example 11, the difference is that 15 mM tris(hydroxymethyl)aminomethane solution is used as the buffer system, and the pH value of the solution is adjusted to 8.

[0146] Embodiment 14

[0147] Compared with Example 11, the difference is that 20 mM tris(hydroxymethyl)aminomethane solution is used as the buffer system, and the pH value of the solution is adjusted to 9.

[0148] The coating prepared in Example 11 was characterized and its performance was verified:

[0149] Platelet adhesion test blood analyzer quantitative analysis and biocompatibility evaluation:

[0150] First, 1 mL of the whole blood containing 3.2%-3.8% sodium citrate as an anticoagulant was taken out as a blank control, and the blank was incubated at 37°C for 6-7 hours. At the same time, the heparin-grafted medical material (Hep) was taken as a control and soaked in 1 mL of the remaining whole blood with the untreated medical material (Bare) and the medical material coated with the hydrophilic polymer coating of Example 2 (pDMSO) and incubated at 37°C for 6-7 hours. The blood cells in different blood samples were quantitatively analyzed by a blood analyzer to obtain the blood cell content adhering to the surface of the medical material, evaluate the anticoagulant effect and biocompatibility of the hydrophilic polymer coating, and compare it with the heparin anticoagulant coating.

[0151] The results are as follows Fig.11 As shown, the results show: Fig.11There is a significant difference in the amount of platelet adhesion on the surface of medical materials coated with hydrophilic polymer coating materials and that of bare materials, providing better anticoagulant performance; and there is no significant difference with heparin anticoagulant coating. The amount of platelet adhesion on the surface of medical materials coated with hydrophilic polymer coating is less than 5%, which is much lower than that of bare materials, and has excellent anticoagulant performance.

[0152] Biofilm adhesion assay:

[0153] The heparin coating and the hydrophilic polymer coating in Example 2 were respectively constructed on the surface of a 14 mm glass slide and then placed in a sterilized 24-well plate. Pseudomonas aeruginosa PAO1 strain was selected to grow into a biofilm. Two PAO1 colonies were cultured in LB (4 mL), and after shaking at 200 rpm for 16 h at 37 ° C, they were diluted 100 times, and cultured again in a shaker for 4 h before being inoculated into a 24-well plate with a coated glass slide, grouped into 1 mL per well, and cultured in a 37 ° C incubator for 72 h, with 700 μL of culture medium replaced every 24 h. Crystal violet staining: The suspension was aspirated, and the remaining biofilm was washed once with PBS (1 mL), and then crystal violet stain (500 μL) was added and cultured for 20 min. After that, the crystal violet stain was aspirated, and the biofilm was washed 3 times with 1 mL PBS. The remaining biofilm stained with crystal violet was dissolved in ethanol (1 mL), and its OD 550 was measured with an ELISA instrument to quantify the bacterial adhesion on different surfaces.

[0154] The results are as follows Fig.12 As shown, the results show: Fig.12 There is a significant difference between the amount of bacteria adhered to the surface of the glass slide (pDMSO) coated with a hydrophilic polymer coating and the bare material (Bare), which is much lower than the amount of bacteria adhered to the bare material surface and lower than the glass slide with a heparin coating (Hep), providing better anti-bacterial adhesion performance. Fig.14 FIG. 4 is a schematic diagram showing the polymer coating of the present invention resisting bacterial adhesion.

[0155] Evaluation of antimicrobial activity:

[0156] The heparin coating and the polymer hydrophilic coating in Example 2 were constructed on the surface of a 14 mm glass slide, respectively, and then placed in a sterilized 24-well plate. Escherichia coli was used to evaluate the antibacterial activity. Two Escherichia coli colonies were cultured in LB (4 mL), and diluted 100 times after shaking at a speed of 200 rpm for 16 h at 37 ° C. After culturing again in a shaker for 4 h, they were inoculated into a 24-well plate with a coated glass slide, and cultured in an incubator at 37 ° C for 24 hours, and the incubated samples were washed twice with sterile PBS and covered with SYTO 9 / propidium iodide staining solution. The sample was placed in the dark at room temperature for 20 minutes, and then gently rinsed once with sterilized PBS. The sample was then imaged using a confocal laser scanning microscope. Live bacteria with intact cell membranes were stained green, while dead bacteria with damaged cell membranes were stained red. Images were collected using 488nm excitation and emission filters of 500 to 550nm (green) and 605 to 720nm (red).

[0157] The results are as follows Fig.13 As shown, the results show: Fig.13 The number of live and dead bacteria on the surface of the glass slide coated with a hydrophilic polymer coating (pDMSO) was significantly reduced compared with that on the heparin-coated glass slide (Hep) and the bare surface (Bare).

[0158] On this basis, it should also be noted that in other embodiments of the present invention, the base material may be plastic, alloy or ceramic.

[0159] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0160] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A polymer functional coating material, characterized in that: The polymer functional coating material has a structure as shown in formula (I): Wherein, R includes any one or a combination of two or more of a group containing a thioether structure, a group containing a sulfonium ion structure, a group containing a sulfoxide structure, a group containing a sulfone structure, a group containing a zwitterionic structure, and a group containing an oligoethylene glycol structure; n is selected from any integer between 1 and 200; x and y represent the molar ratio of the copolymerized units, x+y=1, 0≤x<1, 0<y≤1.

2. A method for preparing a polymer functional coating material, characterized in that: include: A chain transfer agent having a structure of catechol and / or a catechol derivative is mixed with a functional monomer to carry out a reversible addition-fragmentation chain transfer polymerization reaction to prepare a high molecular functional coating material.

3. The preparation method according to claim 2, characterized in that: include: A chain transfer agent having a structure of catechol and / or a catechol derivative, a monomer having a structure of catechol and / or a catechol derivative, and a functional monomer are mixed to carry out a reversible addition-fragmentation chain transfer polymerization reaction to obtain a polymer functional coating material; Preferably, the functional monomers include any one or a combination of two or more of monomers containing thioether structures, monomers containing sulfonium ion structures, monomers containing sulfoxide structures, monomers containing sulfone structures, monomers containing zwitterion structures, and monomers containing oligoethylene glycol structures; Preferably, the molar ratio of the chain transfer agent having a catechol and / or a catechol derivative structure, the monomer having a catechol and / or a catechol derivative structure, and the functional monomer is (1-5): (1-30): (10-200); Preferably, the polymerization temperature of the reversible addition-fragmentation chain transfer polymerization is 70-80° C., and the polymerization time is 6-12 h.

4. The preparation method according to claim 3, characterized in that: The chain transfer agent having a catechol and / or catechol derivative structure has a structure as shown in formula (II):

5. The preparation method according to claim 3, characterized in that: The monomer having a catechol and / or catechol derivative structure has a structure as shown in at least one of formula (III) or formula (IV):

6. A polymer functional coating material prepared by the preparation method according to any one of claims 2 to 5.

7. A polymer functional coating, characterized in that: The coating is obtained by applying the polymer functional coating material according to claim 1 or 6 to the surface of a substrate; the thickness of the coating is 100-2000nm.

8. The method for preparing a polymer functional coating according to claim 7, characterized in that: include: The surface of the substrate is subjected to a hydroxylation hydrophilic modification treatment, and then the polymer functional coating material is applied to the surface of the substrate in a buffer system to obtain the polymer functional coating.

9. The preparation method according to claim 8, characterized in that: The substrate includes any one or a combination of two or more of polyethylene, polypropylene, polyvinyl chloride, polytetrafluoroethylene, expanded polytetrafluoroethylene, polylactic acid, polycarbonate, polyurethane, polystyrene, polysulfone, polyethersulfone, polyacrylonitrile, polymethacrylate, latex, silicone rubber, glass, ceramic, stainless steel, titanium alloy, and nickel-titanium alloy; And / or, the hydroxylation hydrophilic modification treatment comprises: placing the substrate in a vacuum plasma cleaning machine, subjecting the substrate to oxygen plasma treatment under the conditions of a radio frequency power of 100-300 W and a gas flow rate of 100-500 mL / min, to obtain a hydrophilic surface rich in hydroxyl groups; And / or, the buffer system comprises a tris(hydroxymethyl)aminomethane solution buffer system; And / or, the pH value of the buffer system is 8-9.

10. Use of the polymer functional coating material according to claim 1 or 6 or the polymer functional coating according to claim 7 in the field of medical material protection.

Citation Information

Patent Citations

  • Preparation method for biomimetic mussel adhesive used for adhesion on wet surface and underwater curing

    CN103965810A

  • Surface coating polymer, and preparation method and application thereof

    CN110054732A

  • Catechol compound modified polyether, preparation method and application thereof in improving bonding strength of adhesive

    CN111777759A

  • Catechol functional modified fouling release type marine antifouling paint

    CN118652627A

  • Block copolymer comprising catechol ,segment and inorganic nanoparticles coated by said block copolymer, as well as method for producing block copolymer comprising catechol, segment and method for producing inorganic nanoparticles coated by said block copolymer

    US20170008993A1